Comments killed the k-pop star: Social murder of Choi Jin Ri as the case study of contemporary moral panic - Kilanowska, Joanna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
The socially unacceptable behavior of Choi Jin Ri – known professionally as Sulli – resulted in a wave of moral panic which spread among the South Korea netizens. Anti-fans gathered around the artist after her transgressions against the unwritten rules of Korean pop culture industry – a sort of ethos regulating the behavior of idols and their relationships with fans. The conservative society rejected Choi Jin Ri’s feminist ideas, her close relationship with other woman idols, and the sexual innuendo in the content she published on social media. This article constitutes a case study of the Internet and media hate, with particular emphasis on the way in which Internet users’ comments and reactions to Choi Jin Ri’s private life affected both the reception of her work and her mental health, which in consequence lead to the artist’s suicide in 2019. The article discusses the issue of performative hate in the content published by South Korean Internet users by analyzing selected elements of contemporary media landscape – the pursuit of scandal, the increase in media voyeurism, and the loss of privacy among public figures resulting from attempts at satisfying the needs and curiosity of fans – as well as the moral panic mechanisms understood as a social phenomenon facilitated by the structure of contemporary media.